Clinical and molecular characteristics of Kabuki syndrome patients with missense variants—novel features and literature review - Boniel, Snir; Krajewska, Maria; Pyrżak, Beata; Paluchowska, Monika; Majcher, Anna; Zarlenga, Magdalena; Krenke, Katarzyna; Śmigiel, Robert; Jeziorek, Anetta; Szymańska, Krystyna; Szczałuba, Krzysztof (Frontiers in Genetics, 2024)
Kabuki Syndrome (KS) encompasses a spectrum of clinical manifestations, primarily attributed to pathogenic variants in the KMT2D gene. This study aims to elucidate novel features in KS patients with missense variants, contrasting their presentation with both literature-reported cases of patients with missense pathogenic variants as well as other KS patients with truncating pathogenic variants. Employing a survey questionnaire and clinical evaluations, we examined ten KS patients with missense variants, focusing on their dysmorphism characteristics, behavior and psychomotor development. We identified unique features in missense variant patients, including foot hyperesthesia, musicality, and sensory integration disorders. Notably, despite similarities in developmental trajectories, distinct phenotypic traits emerged in missense variant cases, suggesting a potential genotype-phenotype correlation. These findings contribute to a deeper understanding of KS heterogeneity and underscore the importance of genotype-specific characterization for prognostic and therapeutic considerations. Further exploration of genotype-phenotype relationships promises to refine clinical management strategies and enhance patient outcomes in this complex syndrome.